The Performance Analysis of Companies Before and After Merger and Acquisition - Dave, Parth; Thaker, Jayen (Celebes Scholar pg, 2024)
This essay examines the acquirer company's performance in terms of turnover. Financial data and statistical tools have been used to compare performance on certain financial criteria utilizing the most popular corporate restructuring model, known as merger and acquisition. This study compares the financial outcomes of the acquirer company before and after in an effort to determine the substantial impact of merger and acquisition on turnover. The theoretical underpinnings of the strategy, objective, hypothesis, and analysis are discussed in this essay. An analysis of several transactions from diverse industries has been taken into account. According to the study, there is no appreciable impact on company turnover following merger and acquisition.